Targeted Ablation of Distal Cerebrospinal Fluid-Contacting Nucleus Alleviates Renal Fibrosis in Chronic Kidney Disease - Qiu, Minzi; Li, Jiawen; Tan, Lishan; Zhang, Mengbi; Zhou, Guang; Zeng, Tao; Li, Aiqing (Frontiers in Physiology, 2018)
The potential function of distal cerebrospinal fluid-contacting nucleus (dCSF-CNs) in CKD development is poorly understood. We hypothesized that dCSF-CNs might affect the renin-angiotensin system (RAS) in kidney injury progression, with dCSF-CNs ablation potentially alleviating local RAS and renal fibrosis in rats after five-sixths nephrectomy (5/6Nx). Rats were administered artificial cerebrospinal fluid (aCSF) intracerebroventricularly (icv), followed by 5/6Nx or sham operation, or icv administration of Cholera toxin B subunit conjugated with saporin (CB-SAP) was performed for dCSF-CNs lesion before 5/6Nx. The effect of CB-SAP on dCSF-CNs ablation was confirmed by double immunofluorescence staining. RAS component, NOX2 and c-fos levels in the subfornical organ (SFO), hypothalamic paraventricular nucleus (PVN) and hippocampus, as well as tyrosine hydroxylase (TH) and c-fos positive cells in rostral ventrolateral medulla (RVLM) were assessed. Next, the levels of RAS components (angiotensinogen [AGT], angiotensin-converting enzyme [ACE], AngII type 1 receptor [AT1R], angiotensin-converting enzyme 2 [ACE2], Mas receptor), NADPH oxidases (NOX2 and catalase), inflammatory cytokines (monocyte chemotactic protein 1 [MCP-1] and IL-6), fibrotic factors (fibronectin and collagen I) were assessed. Less CB-labelled neurons were found in dCSF-CNs of CB-SAP treated rats compared with 5/6Nx animals. Meanwhile, CB-SAP downregulated AGT, Ang II, AT1R, NOX2, catalase, MCP-1, IL-6, fibronectin and collagen I, and upregulated ACE2 and Mas receptor, compared with CKD rats. More TH and c-fos positive cells were found in RVLM of 5/6Nx rats, but were decreased after dCSF-CNs ablation. Targeted dCSF-CNs ablation might alleviate renal inflammation and fibrosis in chronic kidney injury by inhibiting cerebral and renal RAS/ NADPH oxidase.